2010
DOI: 10.1051/fruits/2010019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot air treatment on postharvest quality of ‘cat Hoa loc’ mangoes

Abstract: -Introduction. Vietnam is among the world's top 20 mango producing countries. In this country, the 'cat Hoa loc' variety is predominant, with 17 692 ha under cultivation with an annual production of 58 471 t; it is considered to be the best mango variety in the Mekong delta. Ripening of the fruit is typically expressed by a skin colour change from green to bright yellow. This variety is highly prized by local and foreign consumers, but subject to different disorders, especially fruit fly infestations. Heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Similar results for acidity (%) were ascribed by McCollum et al (1993) who reported lower acidity in "Keitt" mango fruits heated at 38°C for two days. Our results showed nonsignificant difference for ascorbic acid contents for both cultivars and found contradictory to the earlier findings of Hoa et al (2010) who reported that hot air treatment 47ºC for 120-180 min decreased the ascorbic acid content of fruit as compared to control (untreated). SSC:TA ratio described the actual taste of the fruit and both cultivars displayed significant increase in sugar: acid ratio in fruits treated with VHT.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results for acidity (%) were ascribed by McCollum et al (1993) who reported lower acidity in "Keitt" mango fruits heated at 38°C for two days. Our results showed nonsignificant difference for ascorbic acid contents for both cultivars and found contradictory to the earlier findings of Hoa et al (2010) who reported that hot air treatment 47ºC for 120-180 min decreased the ascorbic acid content of fruit as compared to control (untreated). SSC:TA ratio described the actual taste of the fruit and both cultivars displayed significant increase in sugar: acid ratio in fruits treated with VHT.…”
Section: Discussioncontrasting
confidence: 99%
“…Frontiers in Sustainable Food Systems | www.frontiersin.org sample after 7 days of storage (Hoa et al, 2010). It was noted that the HAT did not noticeably affect the vitamin C and β-carotene content after the treatment (Hoa et al, 2010;Ornelas-Paz and Yahia, 2014).…”
Section: Hot Air and Hot Water Treatmentmentioning
confidence: 99%